Quality attributes of ghee residue prepared using Deoni and Holstein Friesian crossbred cow milk as influenced by method of preparation: Quality attributes of ghee residue - Sangama, Amanchi A; Sharma, Monika; Menon Rekha Ravindra; K Jayaraj Rao; Laxmana Naik N (Indian Journal of Dairy Science, 2023)
Ghee residue (GR) which is a dairy by product was found to be nutrient dense. The ghee residue composition could be affected by clarification temperature, method of preparation of ghee and breed of the cow. So, the present study was conducted to know whether the clarification temperature (110°C and 120°C), methods of ghee preparation (direct cream and creamery butter), breed of the cow (Indigenous Deoni and Holstein Friesian crossbred) can affect the composition of ghee residue. The moisture, protein, fat, lactose and ash content of various ghee residue samples prepared from the milk of Deoni and HF crossbred cows varied from 10.50±0.22 to 14.65±0.1, 13.49±3.37 to 34.17±3.37, 51.61±0.86 to 67.69±0.09, 9.44±0.06 to 14.15±0.22 and 1.89±0.03 to 5.59±0.41%, respectively. Further, the phospholipid content and antioxidant activity varied from 3.18 to 15.09 and 27.04 to 67.86%, respectively. In this study, it was found that temperature of clarification had significant (p<0.05) effect on moisture, lactose, ash, hydroxy methyl furfural (HMF) and browning index. The method of clarification had significant effect on protein, fat, lactose, ash, phospholipids and antioxidant activity. The type of breed also had significant effect on protein, fat and browning index. Thus, it can be concluded that GR’s composition was affected by breed and method of ghee preparation.